Electronic Structure Calculations and Experimental Studies on the Thermal Initiation of the Twin Polymerization Process. Issue 12 (27th December 2017) - Auer, Alexander A.; Bistoni, Giovanni; Kitschke, Philipp; Mehring, Michael; Ebert, Thomas; Spange, Stefan
Abstract: Presented here is a combined computational and experimental study on the thermal initiation process of the twin polymerization. Although thermally initiated twin polymerization offers a versatile scheme for obtaining hybrid organic/inorganic nanocomposite materials, the mechanism for its initiation is very different from the proton‐initiated twin polymerization. In this study, the basic mechanism of the early steps of the polymerization process of 4 H, 4 H′ ‐2, 2′‐spirobi[benzo[ d ][1, 3, 2]dioxasiline] was investigated by using electronic structure calculations in conjunction with experimental differential scanning calorimetry studies. This way, the influences on the thermally initiated twin polymerization process could be analyzed in detail. The previous mechanistic hypotheses are systematically assessed herein to show that, based on the results, a new hypothesis for an initiation mechanism can be formulated that is in agreement with all experimental observations. These results suggest that, before the formation of the polymer networks, the thermal initiation starts with the formation of low‐molecular‐weight fragments that react to yield acidic groups. If a sufficient amount of these form, the reaction is ultimately funneled into a mechanism similar to that of proton‐initiated twin polymerization. Abstract : Hot topic : Twin polymerization is a unique process that yields organic/inorganic nanocomposites in a one‐step procedure from a given precursor monomer. Presented here is a combined computational and experimental study on the thermal initiation of the twin polymerization, an assessment of previous hypotheses, and a conclusive mechanism based on the results.